Reversible stress softening and stress recovery of cellulose networks - Torres, FG (2009)
The authors would like to thank the Direction of Research (DAI) of PUCP, the Science and Technology Council of Peru (CONCYTEC), the Spanish Research Council (CSIC) and the Generalitat Valenciana, Conselleria de Empresa, Universidad y Ciencia (project number ARVIV/2007/101) for financial support.